The Effect of Thymoquinone on the TNF-?/OTULIN/NF-?B Axis Against Cisplatin-İnduced Testicular Tissue Damage - Yalcin, Tuba; Kaya, Sercan; Yigin, Akin; Agca, Can Ali; Ozdemir, Deniz; Kuloglu, Tuncay; Boydak, Murat (Springer Heidelberg, 2024)
One of the adverse effects of the antineoplastic drug cisplatin (CS) is damage to testicular tissue. This study aimed to examine the potential therapeutic effect of thymoquinone (TQ), a strong antioxidant, against testicular damage caused by CS. In the experiment, 28 rats were used, and the rats were randomly divided into four groups: control (n = 7), CS (n = 7), CS + TQ (n = 7), and TQ (n = 7). The experiment was called off after all treatments were finished on day 15. Blood serum and testicular tissues were utilized for biochemical, histological, immunohistochemical, mRNA expression, and gene protein investigations. The testosterone level decreased and oxidative stress, histopathological damage, dysregulation in mitochondrial dynamics, inflammation and apoptotic cells increased in testicular tissue due to CS administration. TQ supplementation showed anti-inflammatory, antioxidant, and anti-apoptotic effects in response to CS-induced testicular damage. In addition, TQ contributed to the reduction of CS-induced toxic effects by regulating the TNF-alpha/OTULIN/NF-kappa B pathway. TQ supplementation may be a potential therapeutic strategy against CS-induced testicular damage by regulating the TNF-alpha/OTULIN/NF-kappa B axis, inhibiting inflammation, oxidative stress, and apoptosis.
Keywords: Nuclear factor kappa B; OTULIN; Cisplatin; Testicular damage; Thymoquinone; Tumour necrosis factor-alpha